Computer analysis of vibrations of hoisting system - Tejszerska, Dagmara (Computer Assisted Methods in Engineering and Science, 1997)
Model of longitudinal vibrations of mine hoist, treated as a discrete-continuous system is formulated. The model includes phenomena connected with variations of the load, carried by each rope and with sliding of the rope contacting with pulley. The effects of changes of length of both branches of rope, variations of their stiffness, internal damping, friction and diversification of parameters of individual ropes in multirope system are taken into account. General model equations, relations describing movement of elementary segments of ropes and of the whole system, and the method of solving the obtained equations are presented in the paper. Nonlinear system of partial and ordinary differential equations is solved numerically. Example results of numerical simulation, showing the possibilities of the formulated model and the program - are presented.